Sustainability and corporate social responsibility in supply chains: The state of research in supply chain management and business ethics journals. Issue 2 (June 2016) - Quarshie, Anne M.; Salmi, Asta; Leuschner, Rudolf
Abstract: Sustainability has become a popular topic, not only in business research at large, but specifically in the supply chain management (SCM) discipline. In addition, the business ethics (BE) field has an extensive stream of literature focusing on supply chain topics. While some exchange of ideas can be witnessed, the two streams developed largely independently. A key purpose of this article is to examine and contrast existing research and knowledge creation, focusing on sustainability and corporate social responsibility (CSR) issues in supply chains, within and across these two disciplines. The in-depth systematic literature review covers 195 articles, published in 12 peer-reviewed journals from 2007 to 2013, examining the methodological and theoretical approaches, as well as the main research focus areas. We found highly complementary research topic areas but only limited synergy and dialogue between the disciplines. The research area at large would benefit from greater integration. Based on our findings, we propose a future research agenda that connects across the disciplines and highlights key areas that would benefit from further inquiry. Highlights: The systematic review covers 195 articles published in 2007–2013 in 12 journals. We examine and contrast research published in SCM and business ethics streams. We find complementary research areas but limited synergy between the disciplines. The study proposes open research gaps and new paths for future research. We also discuss implications for theory development on sustainable supply chains.